Lippia carrascoana (Verbenaceae), an enigmatic new species from the Brazilian Caatinga - Cardoso, Pedro Henrique; Silva, Gabriel Barros Da; Trovó, Marcelo; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2025)
Despite their non-monophyletic status under current circumscriptions, Lantana and Lippia (Lantaneae, Verbenaceae) remain traditionally distinguished by fruit morphology. The former exhibits drupes with a single pyrene, while the second bears schizocarps that split into two cluses or drupaceous fruits with two pyrenes. While examining herbarium collections from Brazil, we discovered a new species of Lantaneae characterized by the unique combination of the following traits: leaf blades with margins entire near the base or up the middle and conspicuously dentate towards the apex, abaxial surfaces covered with abundant sessile glandular trichomes and strigose along the veins, bracts with attenuate or aristate apices, lilac or white corollas lacking eglandular trichomes externally, densely sericeous ovaries, and drupaceous fruits with a pilose external surface. We describe this species as Lippia carrascoana, endemic to the Caatinga domain in the states of Ceará, Pernambuco, and Piauí. It grows in carrasco vegetation on dystrophic red-yellow latosols, at elevations between 500 and 830 m. Although Lippia carrascoana has been collected since 1978, its specimens were either misidentified or identified only at the generic level as Lantana sp. or Lippia sp. The detailed description of the new species is accompanied by illustrations, distribution notes, an occurrence map, as well as comparisons with similar species (Lantana restingensis, Lippia brasiliensis, Lippia magentea, Lippia maximilianii), and some species that, despite being morphologically distinct, have been involved in past misidentifications (Lantana camara, Lantana canescens, Lantana fucata). A preliminary conservation status assessment suggests that Lippia carrascoana qualifies as Endangered (EN).